Efektivitas Pemanfaatan Instagram oleh Pustakawan dalam Meningkatkan Literasi Informasi Masyarakat di Perpustakaan Umum Kabupaten Solok - Afnella, Gita Tria; Marlini, Marlini; Erlianti, Gustina (Lembaga Yasin AlSys, 2026)
Librarians’ use of Instagram has the potential to enhance community information literacy, yet its effectiveness in the context of regional public libraries has not been widely examined empirically. This study aimed to determine the effectiveness of librarians’ use of Instagram in improving community information literacy at the Solok Regency Public Library. A quantitative approach with an explanatory research design was employed, with the population consisting of community members who follow the Instagram account of the Solok Regency Public Library and a sample selected using purposive sampling. Data were collected using a closed Likert-scale questionnaire measuring librarians’ use of Instagram and the level of community information literacy, and were then analysed using descriptive and inferential statistics through simple linear regression. The results showed that librarians’ use of Instagram was in the good category and had a significant effect on community information literacy, as reflected in the increased ability of community members to identify their information needs and to search for, evaluate, and use information effectively. These findings affirm that improving the quality of content, interactivity, and consistency in managing the library’s Instagram account constitutes an effective strategy for strengthening community information literacy. This study provides practical implications for public libraries in optimising the use of social media as a means of enhancing information literacy and user education services.